A Theory of Causation in the Social and Biological Sciences - Reutlinger, A. author. aut Link
XII, 276 p.
Keywords: This first full length treatment of interventionist theories of causation in the social sciences, the biological sciences and other higher-level sciences the presents original counter arguments to recent trends in the debate and serves as useful introduction to the subject.